Adherence to COVID-19 preventive measures among residents in selected townships, Yangon Region, Myanmar: a community-based cross-sectional study - Ye Minn Htun; Nyan Lin Maung; Dwe Kyaw Ko; Han Myo Htut; Min Khant Phyo; Wai Lynn Aung; Hein Khant Zaw; Aung Kyaw Min; Aung Phyo Kyaw; Thet Swe; Kaung Khant Zaw; Kyaw Swar Naing Win; et al. (Tropical Medicine and Health, 2024)
Abstract Background To fight the current coronavirus disease (COVID-19) pandemic, many countries have implemented various mitigation measures to contain the spread of the disease. By engaging with health service providers, the community’s participation in adherence to preventive measures is certainly required in the implementation of COVID-19 mitigation strategies. Therefore, this study aimed to assess the level of adherence to COVID-19 preventive measures and its associated factors among the residents, Yangon Region, Myanmar. Methods A community-based cross-sectional study was carried out among 636 residents in Yangon Region, Myanmar, from October to December 2021. A multistage non-probability sampling method, purposively selected for three townships in Yangon Region and convenience sampling for 212 participants from each township, was applied and the data were collected by face-to-face interviews using structured and pretested questionnaires. Data were entered, coded, and analyzed using IBM SPSS version 25.0. Simple and multiple logistic regression analysis were performed to identify the significant variables of adherence to COVID-19 preventive measures. Results As a level of adherence to COVID-19 preventive measures, the proportion of residents who had good adherence was 39.3% (95% CI 35.5–43.2%), moderate adherence was 37.6% (95% CI 33.8–41.5%), and poor adherence was 23.1% (95% CI 19.9–26.6%). The age group of 31–40 years (AOR: 3.13, 95% CI 1.62–6.05), 30 years and younger (AOR: 3.22, 95% CI 1.75–5.92), Burmese ethnicity (AOR: 2.52, 95% CI 1.44–4.39), own business (AOR: 3.19, 95% CI 1.15–8.87), high school education level and below (AOR: 1.64, 95% CI 1.02–2.69), less than 280.90 USD of monthly family income (AOR: 1.51, 95% CI 1.01–2.29), low knowledge about COVID-19 (AOR: 1.90, 95% CI 1.26–2.88) were significantly associated with poor adherence to COVID-19 preventive measures. Conclusions In this study, nearly one-fourth of the residents were experiencing poor adherence to COVID-19 preventive measures. Therefore, building up the risk communication through the community using widely used mainstream media, the continuation of disease surveillance and announcement of updated information or advice for the public to increase awareness towards COVID-19, and enforcement to follow the recommended directions and regulations of health institutions are vital to consider for improving the adherence to preventive measures against COVID-19 among the residents.